2011
DOI: 10.1111/j.1365-2486.2011.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevated CO2 on growth and competition in experimental phytoplankton communities

Abstract: We report an experiment designed to identify the effect of elevated CO 2 on species of phytoplankton in a simple laboratory system. Major taxa of phytoplankton differ in their ability to take up CO 2 , which might lead to predictable changes in the growth rate of species and thereby shifts in the composition of phytoplankton communities in response to rising CO 2 . Six species of phytoplankton belonging to three major taxa (cyanobacteria, diatoms and chlorophytes) were cultured in atmospheres whose CO 2 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 46 publications
6
84
3
1
Order By: Relevance
“…We used modified Bold's Basal Medium (BBM) with pH adjusted to 7 using HCl , supplemented with silicate (0.58 g l 21 Na 2 SiO 3 ) and vitamins (2 ml l 21 of the vitamin mix from F/2 Medium; for further information on the medium and references see [22]). We allowed the medium to equilibrate with chamber air for 5 days before inoculation.…”
Section: Materials and Methods (A) Selection Experimentsmentioning
confidence: 99%
“…We used modified Bold's Basal Medium (BBM) with pH adjusted to 7 using HCl , supplemented with silicate (0.58 g l 21 Na 2 SiO 3 ) and vitamins (2 ml l 21 of the vitamin mix from F/2 Medium; for further information on the medium and references see [22]). We allowed the medium to equilibrate with chamber air for 5 days before inoculation.…”
Section: Materials and Methods (A) Selection Experimentsmentioning
confidence: 99%
“…Shifts in phytoplankton composition due to ocean acidification (Tortell et al 2002, Low-Décarie et al 2011, Meakin & Wyman 2011 or increased temperatures (Hare et al 2007) are commonly observed experimentally. The impact of ocean acidification on the calcifying coccoli thophores has received special attention.…”
Section: Role Of Phytoplanktonmentioning
confidence: 99%
“…Ecological and evolutionary responses to changing environments are contingent on the community in which the change occurs [6][7][8][9][10]. A population's ability to adapt and persist in changing environments will therefore also hinge on the surrounding community [11] (see also [12]).…”
Section: Introductionmentioning
confidence: 99%
“…But competition can also increase selective pressure [23], speed niche expansion [24][25][26] and increase rates of evolution [27], possibly allowing populations to adapt to new conditions faster. These potentially contrasting effects may account for the unanticipated population dynamics and patterns of persistence in competitive communities [6] (but see [10]). …”
Section: Introductionmentioning
confidence: 99%